Education for hard-to-reach children: strategies used by NGO Surovi to provide primary education to children living in urban slums - Islam, Manisha (Brac University, 2021)
This thesis is submitted in partial fulfilment of the requirements for the degree of Masters of Science in Early Child Development, 2019.